Automatic female dehumanization across the menstrual cycle. (30th November 2016) - Piccoli, Valentina; Fantoni, Carlo; Foroni, Francesco; Bianchi, Mauro; Carnaghi, Andrea
Abstract : In this study, we investigate whether hormonal shifts during the menstrual cycle contribute to the dehumanization of other women and men. Female participants with different levels of likelihood of conception (LoC) completed a semantic priming paradigm in a lexical decision task. When the word 'woman' was the prime, animal words were more accessible in high versus low LoC whereas human words were more inhibited in the high versus low LoC. When the word 'man' was used as the prime, no difference was found in terms of accessibility between high and low LoC for either animal or human words. These results show that the female dehumanization is automatically elicited by menstrual cycle‐related processes and likely associated with an enhanced activation of mate‐attraction goals.